2005
DOI: 10.1111/j.1525-1470.2005.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Xanthoma Disseminatum with Hepatic Involvement in a Child

Abstract: Xanthoma disseminatum is a rare, usually self-healing dermatologic disease of unknown etiology. Involvement of other organs and tissues including bone marrow, bone, and brain may be seen rarely in children. However, to date, hepatic involvement has not been reported. We describe a child with xanthoma disseminatum who had hepatic involvement, and discuss his course and treatment with steroid and azathioprine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Zak et al 8 reported intracranial involvement of XD, which resulted in death of the patient. Büyükavci et al 9 described a case of XD with hepatic involvement, which resulted in sclerosing cholangitis. Mass effects from xanthomas can create serious problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zak et al 8 reported intracranial involvement of XD, which resulted in death of the patient. Büyükavci et al 9 described a case of XD with hepatic involvement, which resulted in sclerosing cholangitis. Mass effects from xanthomas can create serious problems.…”
Section: Discussionmentioning
confidence: 99%
“…As xanthomas were detected on the oral mucosa, an upper and lower gastrointestinal endoscopy and a laryngoscopy were performed, which also revealed nonspecific findings. Histopathological findings of XD can be explained by 9 used mainly oral prednisolone (2 mg/kg/day) and oral azathioprine (2 mg/kg/day), but the patient failed to respond. Further, some have had successful results using a combination of lipid lowering agents or azathioprine and cyclophosphamide 16,18 .…”
Section: Discussionmentioning
confidence: 99%
“…For MCRH, because of the frequent failure of cytotoxic and anti-TNF-α drugs and the risk of associated malignant conditions, an interesting complete remission was obtained with anakinra [18]. Similarly, besides local treatment for isolated and/or accessible lesions in XD, several treatment strategies showed disappointing results (or were successful in isolated cases), including lipid-lowering agents, prednisone, interferon-α, immunosuppressants and chemotherapies (table 1) [20,21,22,23,24,25,26,27,28,29,30,31]. The proposal of anakinra therefore appears adequate in our XD patient, by analogy with its harmless and successful results in ECD and MCRH, on the basis of histological and biological evidence for the leading role of IL-1 cytokines in these last two NLH [3,18].…”
Section: Discussionmentioning
confidence: 99%
“…XD characteristically involves hundreds of symmetrically distributed cutaneous red‐brown papules that rapidly coalesce and become more yellow in colour . Although typically involving the face, trunk, flexural and intertriginous areas, XD may also be present in the central nervous system (CNS), ocular structures, respiratory and gastrointestinal tracts, abdominal organs, musculoskeletal system and bone marrow . The diagnosis of XD relies on pathological findings from the involved lesions and the clinical manifestation.…”
mentioning
confidence: 99%